After‐hours medical deputising services: patterns of use by older people. Issue 9 (7th November 2016) - Joe, Angela; Lowthian, Judy A; Shearer, Marianne; Turner, Lyle R; Brijnath, Bianca; Pearce, Christopher; Browning, Colette; Mazza, Danielle
Abstract: Objectives: To examine how older people use an after‐hours medical deputising service that arranges home visits by locum general practitioners; to identify differences in how people who live in the community and those who live in residential aged care facilities (RACFs) use this service. Design, setting and participants: Retrospective analysis of routinely collected administrative data from the Melbourne Medical Deputising Service (MMDS) for the 5‐year period, 1 January 2008 – 31 December 2012. Data for older people (≥ 70 years old) residing in greater Melbourne and surrounding areas were analysed. Main outcome measures: Numbers and rates of MMDS bookings for acute after‐hours care, stratified according to living arrangements (RACF v community‐dwelling residents). Results: Of the 357 112 bookings logged for older patients during 2008–2012, 81% were for RACF patients, a disproportionate use of the service compared with that by older people dwelling in the community. Most MMDS bookings resulted in a locum GP visiting the patient. During 2008–2012, the booking rate for RACFs increased from 121 to 168 per 1000 people aged 70 years or more, a 39% increase; the booking rate for people not living in RACFs increased from 33 to 40 per 1000 people aged 70 years or more, a 21% increase. Conclusions: After‐hours locum GPs booked through the MMDS mainly attended patients living in RACFs during 2008–2012. Further research is required to determine the reasons for differences in the use of locum services by older people living in RACFs and in the community.